Evaluating Porins OmpK35 and OmpK36 mRNA Expression in Ciprofloxacin-Resistant Klebsiella pneumoniae - Sulistiyawati, Indah; Wahyono, Daniel Joko; Siswandari, Wahyu (Molekul, 2024)
Porin messenger RNA (mRNA) expression significantly influences porin permeability and reduces antibiotic penetration. Klebsiella pneumoniae has developed resistance to several antibiotics. Decreased expression levels of OmpK35 and OmpK36 porins result in changes in the porin profile and even functional loss of porins. This research aimed to analyze the relative expression of the outer membrane porins, OmpK35 and OmpK36. The research methodology involved MIC assays and quantification of OmpK35 and OmpK36 mRNA using RT-qPCR. The relative expression of OmpK35 and OmpK36 in clinical isolate K. pneumoniae is 0.8925 and 0.5877, respectively. The porin permeability of OmpK35/K36 mRNA positively correlated with the MIC values of OmpK35 (p-value = 0.029) and OmpK36 (p-value = 0.016), respectively. Keywords: Ciprofloxacin, Klebsiella pneumoniae, OmpK35/K36, porin permeability